Prevalence of accessory canals in furcation area in primary molar teeth – A systematic review and meta-analysis - Pakhi Piyush Shah; Laresh Naresh Mistry; Anusree Basu (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Aim: The aim of the systematic review was to evaluate the percentage prevalence of accessory canals in furcation area of primary molar teeth. Methodology: Data search was conducted by two independent investigators on online databases PubMed, Cochrane Library, and Semantic Scholar, and then data extraction was done as table under the specific headings. Out of 11 identified studies, 5 were included for systematic review and meta-analysis. MedCalc tool was used for meta-analysis of the data. Forest plots were made for meta-analysis and I2 statistics were used for measuring heterogeneity. The risk of bias was assessed using the QUIN Tool. Results: Of the six studies included, 285 teeth were analyzed for the prevalence of accessory canals. Using random effects model (REM) analysis, the estimated pooled prevalence was 68% (95% confidence interval [CI] 56.57–78.60) with heterogeneity of 76%. Two subgroup meta-analyses was carried out. Using fixed effects model (FEM) analysis, the method for evaluating prevalence according to scanning electron microscopy was 59.4% (95% CI 51.96–66.60) with heterogeneity of 47%; using fixed effect model (REM) analysis, the method for evaluating prevalence according to light microscopy was 71.07% (95% CI 59.19–81.16) with heterogeneity of 39%. There was moderate risk of bias across studies. Conclusion: Prevalence percentage of accessory canals in furcation area was 68% when measured at external furcation area. Evidence was of low quality with high heterogeneity. This suggests the possible contribution of furcation area and its treatment in endodontic treatment of primary molars.